Totally Generalized *Co finitely Supplemented Modules - Khalid Hassan, Wasan; Allah Dnan, Raid Hasb (Iraqi Journal of Science, 2023)
Let R be an associative ring with identity, and let M be a unital left R-module, M is called totally generalized *cofinitely supplemented module for short ( T G*CS), if every submodule of M is a Generalized *cofinitely supplemented ( G*CS ). In this paper we prove among the results under certain condition the factor module of T G*CS is T G*CS and the finite sum of T G*CS is T G*CS.